2015
DOI: 10.1016/j.laa.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Explicit upper bounds for the spectral distance of two trace class operators

Abstract: Given two trace class operators A and B on a separable Hilbert space we provide an upper bound for the Hausdorff distance of their spectra involving only the distance of A and B in operator norm and the singular values of A and B. By specifying particular asymptotics of the singular values our bound reproduces or improves existing bounds for the spectral distance. The proof is based on lower and upper bounds for determinants of trace class operators of independent interest.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In [35], it is shown that in general, there is no convergence of spectra and it is determined, for which subsets K of C there exists a filtration {P n } such that d H (σ(T n ), K) → 0 as n → ∞, where d H denotes the Hausdorff distance. On the other hand, there are also some positive results assuring the convergence of σ(T n ) to σ(T ) under some restrictive hypotheses, see [24,6] and references in [6]. Proposition 4.2 in [10] contains an abstract result on the partial limit set of ε-pseudospectra of T n , under certain hypotheses.…”
Section: General Theorems On Convergencementioning
confidence: 99%
“…In [35], it is shown that in general, there is no convergence of spectra and it is determined, for which subsets K of C there exists a filtration {P n } such that d H (σ(T n ), K) → 0 as n → ∞, where d H denotes the Hausdorff distance. On the other hand, there are also some positive results assuring the convergence of σ(T n ) to σ(T ) under some restrictive hypotheses, see [24,6] and references in [6]. Proposition 4.2 in [10] contains an abstract result on the partial limit set of ε-pseudospectra of T n , under certain hypotheses.…”
Section: General Theorems On Convergencementioning
confidence: 99%